Single Tungsten Atoms Supported on MOF‐Derived N‐Doped Carbon for Robust Electrochemical Hydrogen Evolution - Chen, Wenxing; Pei, Jiajing; He, Chun‐Ting; Wan, Jiawei; Ren, Hanlin; Wang, Yu; Dong, Juncai; Wu, Konglin; Cheong, Weng‐Chon; Mao, Junjie; Zheng, Xusheng; Yan, Wensheng; et al. (Advanced materials (Weinheim), 2018)
Tungsten‐based catalysts are promising candidates to generate hydrogen effectively. In this work, a single‐W‐atom catalyst supported on metal–organic framework (MOF)‐derived N‐doped carbon (W‐SAC) for efficient electrochemical hydrogen evolution reaction (HER), with high activity and excellent stability is reported. High‐angle annular dark‐field scanning transmission electron microscopy (HAADF‐STEM) and X‐ray absorption fine structure (XAFS) spectroscopy analysis indicate the atomic dispersion of the W species, and reveal that the W1N1C3 moiety may be the favored local structure for the W species. The W‐SAC exhibits a low overpotential of 85 mV at a current density of 10 mA cm−2 and a small Tafel slope of 53 mV dec−1, in 0.1 m KOH solution. The HER activity of the W‐SAC is almost equal to that of commercial Pt/C. Density functional theory (DFT) calculation suggests that the unique structure of the W1N1C3 moiety plays an important role in enhancing the HER performance. This work gives new insights into the investigation of efficient and practical W‐based HER catalysts. A single‐tungsten‐atom catalyst supported on metal–organic framework‐derived N‐doped carbon is reported. The catalyst demonstrates a high activity and excellent stability for efficient electrochemical hydrogen evolution.